Travel patterns, regarding different activities: work, studies,se en household responsibilities and leisure - Olmo-Sánchez, María Isabel; Maeso-González, Elvira (Elsevier, 2014)
This study provides a descriptive analysis of the relationship between mobility and gender through unravel the complex relationships between gender roles at home (household responsibilities), leisure and the labor market (employment status). Specifically we study both the average number of journeys by different daily activities and the distances and average time spent on them. Thus, the spatio-temporal patterns of these activities allow us to identify different socio demographic variables that may help explain the relative differences in the behavior of journeys to different activities. The results highlight that, women perform more trips than men regardless of the reason. Moreover, the difference between the number of trips by gender is greater when the reason for the trip is about household responsibility. Regarding the influence of socio-demographic variables the study reveals that in general, the reason why men and women travel greater distances is due to work. One interesting result is that employed women travel considerably shorter distances to work than do men even though they spend similar commute time. This suggests that, the journey to work may reflect the magnitude of immobility that women face in their everyday lives. On the other hand, the socio-demographic characteristics analyzed (size and population density, household income, etc...) condition mainly women's travel patterns.
Keywords: Turismo; Gender; Travel patterns; Household responsibility